2016
DOI: 10.1096/fj.201600820r
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel therapeutic vaccine carrier that sustains high antibody titers against several targets simultaneously

Abstract: With the aim to improve the efficacy of therapeutic vaccines that target self-antigens, we have developed a novel fusion protein vaccine on the basis of the C-terminal multimerizing end of the variable lymphocyte receptor B (VLRB), the Ig equivalent in jawless fishes. Recombinant vaccines were produced in by fusing the VLRB sequence to 4 different cancer-associated target molecules. The anti-self-immune response generated in mice that were vaccinated with VLRB vaccines was compared with the response in mice th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The monomeric VLR67 and VLR76 migrated as monomeric units at approximately ∼ 40 kDa under both nonreducing and reducing conditions, and these monovalent VLRBs showed no reactivity to the Ags, NNV, VHSV, and AIV, as expected ( Fig. 1D) (27,28). These results indicated that the Ag binding ability of the multimerized form of VLRBs was much higher than that of monomeric VLRBs.…”
Section: Selection Of Ag-specific Recombinant Vlrbssupporting
confidence: 60%
“…The monomeric VLR67 and VLR76 migrated as monomeric units at approximately ∼ 40 kDa under both nonreducing and reducing conditions, and these monovalent VLRBs showed no reactivity to the Ags, NNV, VHSV, and AIV, as expected ( Fig. 1D) (27,28). These results indicated that the Ag binding ability of the multimerized form of VLRBs was much higher than that of monomeric VLRBs.…”
Section: Selection Of Ag-specific Recombinant Vlrbssupporting
confidence: 60%
“…This approach makes use of conjugation of the target of interest to a foreign protein, such as the truncated form of bacterial thioredoxin (TRXtr) [ 10 ]. The conjugate vaccine technology has been shown to efficiently induce an antibody-based immune response against vascular-specific self-proteins [ 7 , 8 , 10 , 11 , 12 ]. It is important to mention that in addition to an efficient immunization strategy, the co-administration of a potent adjuvant is needed to generate this immune response.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the C-terminal multimerizing end of VLRB was fused to cancer relevant vaccine targets, creating a multimeric vaccine with minimal exposed VLR sequence. These properties resulted in a more effective vaccine with higher Ab titer against the vaccine target and lower Ab titer against the VLR component compared with other carrier strategies [44].…”
Section: Engineering Of Vlrs For Downstream Applicationsmentioning
confidence: 99%